Global distribution and conservation of marine mammals - Pompa, Sandra (National Academy of Sciences, 2011)
We identified 20 global key conservation sites for all marine (123) and freshwater (6) mammal species based on their geographic ranges. We created geographic range maps for all 129 species and a Geographic Information System database for a 46,184 1° x 1° grid-cells, ∼10,000-km(2). Patterns of species richness, endemism, and risk were variable among all species and species groups. Interestingly, marine mammal species richness was correlated strongly with areas of human impact across the oceans. Key conservation sites in the global geographic grid were determined either by their species richness or by their irreplaceability or uniqueness, because of the presence of endemic species. Nine key conservation sites, comprising the 2.5% of the grid cells with the highest species richness, were found, mostly in temperate latitudes, and hold 84% of marine mammal species. In addition, we identified 11 irreplaceable key conservation sites, six of which were found in freshwater bodies and five in marine regions. These key conservation sites represent critical areas of conservation value at a global level and can serve as a first step for adopting global strategies with explicit geographic conservation targets for Marine Protected Areas.